Improvement of Community Capacity in Managing the Cetho Tourist Destination in Gumeng Jenawi Village, Karanganyar, Central Java - Sidik Jatmika; Muhammad Zahrul Anam (Institut Teknologi dan Bisnis Asia Malang, 2023)
Purpose: This research paper aims to investigate enhancing community capacity in managing the Cetho Tourist Destination in Gumeng Jenawi Village, Karanganyar, Central Java. It highlights the significance of this research in fostering tourism development within the region. Method: The study employed a comprehensive research methodology, which involved field visits, observation, discussions, and documentation. Various cultural symbols of Javanese culture were utilized, and a Focus Group Discussion was conducted with 15 stakeholders involved in Gumeng Tourism Village management. Data analysis was carried out using the SWOT analysis method to guide the development of the tourism village. Practical Applications: The findings of this study have practical implications for the tourism industry and community development in the Gumeng Jenawi Village area. They can be applied to enhance the attraction and visitor numbers while extending their length of stay, ultimately benefiting the local economy and the tourism sector. Conclusion: In conclusion, this research emphasizes the importance of strengthening community capacity for the sustainable management of tourist destinations. The study's results contribute to a broader understanding of improving tourist attractions and their potential impact on local communities and the tourism industry.